2013
DOI: 10.1038/nn.3504
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation regulates associative reward learning

Abstract: Reward-related memories are essential for adaptive behavior and evolutionary fitness, but are also a core component of maladaptive brain diseases such as addiction. Reward learning requires dopamine neurons located in the ventral tegmental area (VTA), which encode relationships between predictive cues and future rewards. Recent evidence suggests that epigenetic mechanisms, including DNA methylation, are essential regulators of neuronal plasticity and experience-driven behavioral change. However, the role of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
199
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(203 citation statements)
references
References 53 publications
(82 reference statements)
4
199
0
Order By: Relevance
“…During the past few decades we have learned how vital epigenetic processes are for learning and memory formation (Day et al 2013). RNA modifications form an additional language, much less characterized, which is capable of overwriting and redefining the hard-wired transcriptome, extending and diversifying the function of transcripts, thus adding an unchartered layer of regulation affecting genome function.…”
Section: Discussionmentioning
confidence: 99%
“…During the past few decades we have learned how vital epigenetic processes are for learning and memory formation (Day et al 2013). RNA modifications form an additional language, much less characterized, which is capable of overwriting and redefining the hard-wired transcriptome, extending and diversifying the function of transcripts, thus adding an unchartered layer of regulation affecting genome function.…”
Section: Discussionmentioning
confidence: 99%
“…bdnf and reelin) show methylation changes after contextual fear conditioning, appetitive auditory conditioning or LTP induction in hippocampal slices (Levenson et al, 2006;Lubin et al, 2008;Miller and Sweatt, 2007;Day et al, 2013). Suggesting them to be potentially regulated by DNA methylation during memory formation.…”
Section: Dna Methylation and Demethylation In Behavioural Plasticitymentioning
confidence: 99%
“…reward) conditioning (Day et al, 2013). These studies investigated a range of different brain areas such as the hippocampus (Levenson et al, 2006;Miller and Sweatt, 2007;Miller et al, 2008;Lubin et al, 2008;Hutnick et al, 2009;Sultan et al, 2012;Mizuno et al, 2012;Rudenko et al, 2013;Kaas et al, 2013;Morris et al, 2014), the amygdala (Maddox and Schafe, 2011;Sultan et al, 2012;Monsey et al, 2011;Morris et al, 2014;Kumar et al, 2015) and the cortex (Hutnick et al, 2009;Miller et al, 2010;Sui et al, 2012;Rudenko et al, 2013).…”
Section: Dna Methylation and Demethylation In Behavioural Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Together, both approaches have demonstrated that DNA methylation is necessary for memory formation and consolidation (Day et al, 2013;Feng et al, 2010;Maddox & Schafe, 2011;Miller & Sweatt, 2007) with a reduction in DNA methylation leading to enhanced glutamatergic synaptic scaling (Meadows et al, 2015) and increased neuronal excitability (Meadows et al, 2016).…”
Section: Dna Methylation and The Regulation Of Neural Activitymentioning
confidence: 99%